PENGARUH ALIANSI AUKUS TERHADAP DINAMIKA KETEGANGAN REGIONAL DI LAUT TIONGKOK SELATAN - Sari, Nadia Puspita; ,, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the impact of the Australia–United Kingdom–United States (AUKUS) trilateral security alliance on the dynamics of security tensions in the South China Sea. The establishment of AUKUS in 2021 marked a significant shift in the Indo-Pacific security configuration amid intensifying strategic rivalry between the United States and China. This study aims to examine the effects of AUKUS on threat perceptions, the responses of Southeast Asian countries, and regional security tensions. It employs a qualitative descriptive approach using secondary data from books, academic journals, policy reports, official government documents, and statements by state actors. The analysis is grounded in Regional Security Complex Theory and a constructivist perspective. The findings indicate that AUKUS strengthens Australia’s defense capabilities while heightening China’s threat perceptions and generating fragmented responses among ASEAN states, thereby increasing the complexity and sensitivity of security dynamics in the South China Sea. Keywords: AUKUS, South China Sea, Security Tensions, ASEAN.